2017
DOI: 10.1177/0271678x17725673
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminovascular calcitonin gene-related peptide function in Cacna1a R192Q-mutated knock-in mice

Abstract: Familial hemiplegic migraine type 1 (FHM1) is a rare migraine subtype. Whereas transgenic knock-in mice with the human pathogenic FHM1 R192Q missense mutation in the Cacna1a gene reveal overall neuronal hyperexcitability, the effects on the trigeminovascular system and calcitonin gene-related peptide (CGRP) receptor are largely unknown. This gains relevance as blockade of CGRP and its receptor are therapeutic targets under development. Hence, we set out to test these effects in FHM1 mice. We characterized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The α1A (CACNA1A) subunit is mainly expressed in the nervous tissue of the brain and involves the transmission of synaptic signals in the central nervous system. Research on rat models has shown that abnormal expression of the CACNA1A gene can lead to the desensitization of calcitonin gene-related peptide (CGRP) receptors, which are critical in maintaining the systolic response of cerebrovascular smooth muscle [27,28]. In addition, Hu Z et al also reported the association between CACNA1A polymorphisms (rs8182538) and hypertension in Chinese Han [15].…”
Section: Discussionmentioning
confidence: 99%
“…The α1A (CACNA1A) subunit is mainly expressed in the nervous tissue of the brain and involves the transmission of synaptic signals in the central nervous system. Research on rat models has shown that abnormal expression of the CACNA1A gene can lead to the desensitization of calcitonin gene-related peptide (CGRP) receptors, which are critical in maintaining the systolic response of cerebrovascular smooth muscle [27,28]. In addition, Hu Z et al also reported the association between CACNA1A polymorphisms (rs8182538) and hypertension in Chinese Han [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although an homeostatic role for neuroinflammation has been postulated, it might also lead to further release of pro-inflammatory mediators by surrounding activated glial cells, namely reactive astrocytes and microglia, which in turn may trigger or aggravate an underlying pathological condition [4]. Notably, in primary cultures from from postnatal day 11 trigeminal ganglia tissue (containing a mix of trigeminal ganglion neurons and satellite glial cells) of FHM1 mutant mice, satellite glial cells exhibit an increased release of inflammatory mediators and an up-regulation of specific pro-algogenic receptors [5], but it is questionable whether findings in cultured cells can be translated to the intact trigeminal ganglion as no such increases were observed in isolated trigeminal ganglia from mice that were 11-14 weeks old [6]. In addition, trigeminal infiltration of macrophages was observed, pointing to the development of neuroinflammation in the peripheral nervous system [7].…”
Section: Introductionmentioning
confidence: 99%
“…The α1A (CACNA1A) subunit is mainly expressed in the nervous tissue of the brain and involves the transmission of synaptic signals in the central nervous system. Research on rat models has shown that abnormal expression of the CACNA1A gene can lead to the desensitization of calcitonin gene-related peptide (CGRP) receptors, which are critical in maintaining the systolic response of cerebrovascular smooth muscle[27,28].In addition, Hu Z et al also reported the association between CACNA1A polymorphisms (rs8182538) and hypertension in Chinese Han[15].…”
mentioning
confidence: 99%